Desain Ruangan dan Tata Letak Barang Kerja pada Warehouse Electric dan Instrument Menggunakan Metode Analisa System Kerja dan Ergonomi - Khoerun Nisa Safitri; Nurul Aini; Anggi Pramana Syahputra (Jurnal Liga Ilmu Serantau, 2024)
This research aims to redesign and reorganize work stations in the Electric and Instrument Warehouse at XYZ Company using the Work System and Ergonomics Analysis Method. Several aspects that are focused on in this research include the actual work station design, work station layout design, sitting work station design, and qualitative visual displays. The analysis was carried out to overcome the problem of lack of space for movement and comfort when working caused by a non-optimal layout. In the proposed changes, researchers made adjustments to the layout of desks, cabinets or cupboards, computer equipment, shelves, added dividers and doors in the office, and increased the size of the work area. Apart from that, several chairs were also replaced to support a good work attitude. The redesign of the workstation is based on the principles of ergonomics by prioritizing effectiveness, comfort, safety, health and efficiency (ENASE). This adjustment is carried out by paying attention to anthropometric and ergonomic aspects in terms of layout, type and size of facilities.